2019
DOI: 10.1002/zaac.201900091
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nitro‐Octaaza Derivatives of Reduced Anthracene

Abstract: Nitro compounds of octaaza derivatives of reduced anthracene were synthesized for the first time by reaction of 2,3,4a,6,7,8a,9,10‐octaaza‐4,8‐dioxo‐3,4,4a,7,8,8a,9,9a,10,10a‐decahydroanthracene with nitric acid, mixed nitric acid/sulfuric acid, and nitric acid/acetic anhydride at between –20 and –30 °C. In addition, 1,2,4,5‐tetrazine azido derivatives were obtained by hydrolytic decomposition of the starting compound by nitrous acid. All the resultant compounds exhibit high thermal stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…It is seen in Figure 2 that the 1 H NMR spectrum of the obtained sample of compound 3 has no singlet protons of the NH 2 group of the starting bis(hydrazone)glyoxal at 6.59 ppm, while the characteristic signal for the double-bond proton shifts to 5.76 ppm due to the impact of the dinitrourea anion, in which case a characteristic triplet corresponding to the NH 3 + cation protons shows up at 6.96-7.22 ppm [25]. The splitting of the signal into a few equivalent peaks suggests an interaction between the proton in question and the other non-equivalent protons.…”
Section: Synthetic Approachesmentioning
confidence: 95%
See 2 more Smart Citations
“…It is seen in Figure 2 that the 1 H NMR spectrum of the obtained sample of compound 3 has no singlet protons of the NH 2 group of the starting bis(hydrazone)glyoxal at 6.59 ppm, while the characteristic signal for the double-bond proton shifts to 5.76 ppm due to the impact of the dinitrourea anion, in which case a characteristic triplet corresponding to the NH 3 + cation protons shows up at 6.96-7.22 ppm [25]. The splitting of the signal into a few equivalent peaks suggests an interaction between the proton in question and the other non-equivalent protons.…”
Section: Synthetic Approachesmentioning
confidence: 95%
“…The free protons on the nitrogen atoms at positions 3, 7 (the amide ones) and 9, 10 (the amine ones) were theoretically capable of being protonated with acid to generate the respective di-or tetranitro derivatives or salts. However, the previous studies showed that the basicity of the amide nitrogen was lowered by the impact of the electron-withdrawing carbonyl, and the amine protons of the central ring were involved in salt formation (Scheme 4) [25]. A similar reaction using dinitramic acid afforded 2,3,4а,6,7,8а,9,10-octaaza-4,8-dioxo-3,4,4a,7,8,8а,9a,10а-octohydroanthracene-9,10-ion-bis (dinitramide) (4), a high-melting crystalline compound in a 53% yield (Scheme 5).…”
Section: Synthetic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 4-Nitrosemicarbazide reacts with glyoxal (dialdehyde) and diacetyl (diacetone) to yield the respective linear glyoxal bis(nitrosemicarbazone) and diacetyl bis(nitrosemicarbazone). 5 The resultant compounds can be used in further synthesis of novel cyclic nitro compounds 6,7 and bioactive substances. 8 In light of the aforesaid background, a logical question arises as to which compounds will be formed by the reaction between 4-nitrosemicarbazide and 1,3-dicarbonyl compounds since it is well known that the reaction of carbonic acid hydrazide derivatives (semicarbazide, 1,3-diaminourea, etc.)…”
Section: ■ Introductionmentioning
confidence: 99%
“…Despite a few binding sites, the molecule of 4-nitrosemicarbazide exhibits regioselectivity toward monoaldehydes to yield the respective nitrosemicarbazones. , 4-Nitrosemicarbazide reacts with glyoxal (dialdehyde) and diacetyl (diacetone) to yield the respective linear glyoxal bis (nitrosemicarbazone) and diacetyl bis (nitrosemicarbazone) . The resultant compounds can be used in further synthesis of novel cyclic nitro compounds , and bioactive substances …”
Section: Introductionmentioning
confidence: 99%